Interstitial fibrosis is associated with increased COL1A2 transcription in AA-injured renal tubular epithelial cells in vivo. - Fragiadaki, M; Witherden, A; Kaneko, T; Sonnylal, S; Pusey, C; Bou-Gharios, G; Mason, R (2011)
Accumulation of type I collagen is a key event in renal interstitial fibrosis. As there is no effective treatment, understanding the site where collagen is transcribed and the factors driving it in response to disease in vivo is critical for designing future therapies. The present research investigated the transcriptional activity of the COL1A2 gene in a mouse model of progressive fibrosis induced by aristolochic acid (aristolochic acid nephropathy, AAN). To achieve this we genetically modified mice to express a reporter gene (LacZ) and CCN2 (connective tissue growth factor) under the transcriptional control of the COL1A2 promoter /enhancer sequences. Using these mice we asked where is collagen actively transcribed and secondly, what is the role of CCN2 in AAN. Here, we report that de-novo transcription of the COL1A2 gene occurred predominantly in damaged tubular epithelial cells during progressive interstitial fibrosis in vivo. The activation of COL1A2 was studied by detection of the reporter gene LacZ and COL1A2 mRNA in interstitial, glomerular, vascular, and tubular epithelial tissue from laser capture microscopy. We also demonstrated that LacZ-positive cells co-express E-Cadherin a marker of epithelial origin which is consistent with an epithelial phenotype which is capable of collagen expression during injury. There was no evidence of detachment of these cells from tubules to become myofibroblasts. Moreover, we showed that the transgenic mice show a modest enhancement of CCN2 expression; however fibrosis induced by AA is the same in transgenics and controls suggesting that CCN2, at this level of expression, is not sufficient to enhance fibrogenesis. Overall our study provides a better understanding into the expression patterns and roles of two major extracellular matrix proteins: type I collagen and CCN2.